PKM KELOMPOK PENGELOLA WISATA PEMANCINGAN PADA TAMBAK IKAN NILA DI DESA TAMANGAPA KECAMATAN MA’RANG KABUPATEN PANGKEP - Tang, Beddu; Jayadi, Jayadi; Tajuddin, Mustamin; Nursyahran, Nursyahran (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, 2023)
One type of natural resource that is very high in value in Ma'rang District and Tamangapa Village in particular is a large pond land and has a very large economic value, especially shrimp and fish farming. The purpose of this activity is 1) Providing counseling on community empowerment efforts through fishing tourism efforts to improve the living standards of partners. 2) Conduct training on tilapia farming techniques on ponds. This service activity is carried out from October to December 2022 in Tamangapa Village, Ma'rang District, Pangkep Regency. The method used in service is the participatory counseling and training method, which involves as much as possible the participation of the partner community in lectures, discussions, and practices of product design and creation of works. The result that has been achieved from community service activities is that they can know and understand how to manage a fish fishing business in a pond. The pond that is used as a fishing tourist spot is a pond that has been stocked with tilapia seeds and is equipped with fishing facilities such as seating or gazebos so that tourists feel comfortable fishing. The results of the service that has been carried out show that income through fishing tourism can reduce the failure of tilapia farmers in the Tamangapa Village area, so this fishing business needs to continue to be developed and managed properly.